Only one Earth: The care and maintenance of a small planet - Barbara Ward (W. W. Norton, 1972)
This is an unofficial report commissioned by the Secretary General of the United Nations Conference on the Human Environment, prepared with the assistance of a 152 member committee of corresponding consultants in 58 countries.